ANALISIS DEBIT PUNCAK DAS PADANG GUCI KABUPATEN KAUR PROVINSI BENGKULU - Amri, Khairul; Syukron, Ahmad (SIPIL, 2014)
This research aims to determine how much the peak discharge (maximum) discharge that occurredin the catchment area Padang Guci of regency Kaur province Bengkulu. by analyzing the rainfalldata. The method of rainfall analysis with Melchior method is a statistical analysis of thehydrology in a way that aims to predict the peak (maximum) discharge with the specific timereturn. Estimation of the peak (maximum) discharge in this manner using the maximum dailyrainfall data for 20 years to be analyzed in stages starting from the calculations StatisticalParameter, Determination of Distribution Type, Test Match Distribution, Rainfall Design, to obtainthe value of Time of Concentration (Tc). The exact distribution pattern to the rainfall data was LogPerson III. From the research that has been done, for over 2 years old at the time the maximumdischarge in the catchment area Padang Guci at 162,957 m3/second. Keywords: Rainfall, Peak Discharg, catchment area, Melchior method.